Critical comparison between the ancient and the digital storytelling practices: An epistemological analysis - Fakira Mohan Nahak (Communications in Humanities and Social Sciences, 2022)
Storytelling in native languages is an integral part of human life. This art form has been existing since immemorial times in India. In Indian society in general and in Odia society in particular the grandparents/parents used to play a key role in telling stories to their grandchildren. By virtue of their wisdom, they used to adopt the stories from the ancient texts to the contemporary needs and societal and family contexts. The oral practice that transcends spatiotemporal offers many insights to the kids through the informing and enlightening process. The present study is an engagement with the critical comparison between the ancient and the modern (digital) storytelling practices to find out which practice is more effective in transforming the kids into more ethical and responsible citizens. The present study applied an epistemological analysis to examine both the above pedagogical practices in relation to their effectiveness in boosting the creative and imagination levels to next higher levels. The study conducted several open ending interviews with the elders who engaged their kinds with the ancient stories and the modern practitioners involved in storytelling through digital platforms such as YouTube. After examining the contentions put forward by various stakeholders in the process of storytelling, the study showed that the ancient system of storytelling still has many advantages in enlightening the kids over the digital platforms of technological advancement notwithstanding.